-6+8(x-5)=15x+4-7x

Simple and best practice solution for -6+8(x-5)=15x+4-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+8(x-5)=15x+4-7x equation:



-6+8(x-5)=15x+4-7x
We move all terms to the left:
-6+8(x-5)-(15x+4-7x)=0
We add all the numbers together, and all the variables
8(x-5)-(8x+4)-6=0
We multiply parentheses
8x-(8x+4)-40-6=0
We get rid of parentheses
8x-8x-4-40-6=0
We add all the numbers together, and all the variables
-50!=0
There is no solution for this equation

See similar equations:

| (2+w)(3w+7)=0 | | 7(7+5x)=49 | | 5(3x-1)=65 | | 7x-21=7x+1-38 | | 8z+7=0 | | 5a+4=3a+7 | | x-4x+4=1 | | 25^(z-2)=125 | | F(x)=4(4)^x | | 14=y+14 | | 6m+2(m+2)=m-14 | | 4x+4x=-4 | | x+2x+1=121 | | 2z+5=3 | | 6(7n-2)=28 | | -4.1-7.9=6.9n-5.9n+0.3 | | 4a+2=24-6 | | 4v+3-5v=34 | | 30,000-12.5x=0 | | 85+x-36=60 | | 0=3u-24 | | -15=12v-16 | | 2x²-12x+7=0 | | -9-8=7x+5-6x | | 27+3y-11=13y-12-3y | | -8x=3=-37 | | 12d=12 | | x=0.1x=-26.4 | | x=0.1x=-26.4 | | (1/125)^(24-x^2)=5^15x | | (1/125)^24-x^2=5^15x | | .1y+.5y=7.5 |

Equations solver categories